The Relations of Religions and Democracy: The Perspective of Indonesians Living in Germany - Muhammad Azhar (Jurnal Impresi Indonesia, 2025)
This paper is a continuation of the previous research theme concerning the relations between religions and democracy in America; however, the focus has shifted to the German setting. The concept of democracy, which notably originated in the West, embodies a distinctive weltanschauung whereby its implementation can adapt to the society in which it exists, including the culture and political systems that the state follows; this adaptation may differ from one country to another. The specific purpose of this paper is to explore how religious textuality manifests within German society and to examine the current relations between religions and democracy. The research materials for this study are exclusively drawn from the perspectives of Indonesian citizens currently residing in various regions of Germany. This paper employs an interview method and distributes questionnaires containing 18 questions among seven Indonesian citizens living in both Western and Eastern Germany. The findings presented here reveal how the dynamics among Christianity’s Catholic and Protestant adherents have evolved and how these dynamics presently relate to democracy in the country.